The Role of International Research in Teaching Natural Sciences in Primary Grades - G’aniyeva Gulhayo Islom qizi (International Journal on Integrated Education, 2023)
Today, the need to implement large-scale reforms in the field of improving natural science teaching on the basis of multimedia tools, international assessment programs and improving the natural-scientific literacy of students in the classroom is growing. In the UN agreement on education, science and culture "Import of materials of educational, spiritual and cultural content", creating broad conditions for the quality of education of learners worldwide, education It is of particular importance to carry out scientific and research work on the introduction of modern innovative technologies into the glue process. In this regard, achieving efficiency and increasing the role and influence of multimedia tools, conceptual study and analysis of existing problems determine the relevance of the topic.